2002
DOI: 10.1080/07388550290789450
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnology of Microbial Xylanases: Enzymology, Molecular Biology, and Application

Abstract: Xylanases are hydrolases depolymerizing the plant cell wall component xylan, the second most abundant polysaccharide. The molecular structure and hydrolytic pattern of xylanases have been reported extensively and the mechanism of hydrolysis has also been proposed. There are several models for the gene regulation of which this article could add to the wealth of knowledge. Future work on the application of these enzymes in the paper and pulp, food industry, in environmental science, that is, bio-fueling, effluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
282
3
19

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 561 publications
(310 citation statements)
references
References 128 publications
6
282
3
19
Order By: Relevance
“…These enzymes degrade plant fibers made of xylan hemicellulose producing xylose monomers. One of the most important xylanase applications is the pretreatment of pulps, prior to bleaching, in pulp and paper industries (12). These enzymes release lignin fragments by hydrolyzing residual xylan and the pretreatment with xylanase reduces the usage of chlorine as the bleaching agent.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes degrade plant fibers made of xylan hemicellulose producing xylose monomers. One of the most important xylanase applications is the pretreatment of pulps, prior to bleaching, in pulp and paper industries (12). These enzymes release lignin fragments by hydrolyzing residual xylan and the pretreatment with xylanase reduces the usage of chlorine as the bleaching agent.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed by Dahlman et al (2003) showed that the surface of fiber pulps from softwood and hardwood have higher molecular masses xylan polymers and lower frequency of uronic acid side groups. Xylanases from a wide variety of fungal species have been reported to have potential application in the pulping and bleaching processes (Salles et al 2000;Subramaniyan and Prema 2002;Viikari et al 1990). The use of xylanases in prebleaching of cellulose pulp has become an alternative approach in eliminating chlorine in bleaching and reducing chlorinated organic compounds in bleach plant effluents, reduce the kappa number (residual lignin content in the pulp) and increase the brightness of the pulp (Filho 1998;Subramaniyan and Prema 2002;Techapun et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Xylanases from a wide variety of fungal species have been reported to have potential application in the pulping and bleaching processes (Salles et al 2000;Subramaniyan and Prema 2002;Viikari et al 1990). The use of xylanases in prebleaching of cellulose pulp has become an alternative approach in eliminating chlorine in bleaching and reducing chlorinated organic compounds in bleach plant effluents, reduce the kappa number (residual lignin content in the pulp) and increase the brightness of the pulp (Filho 1998;Subramaniyan and Prema 2002;Techapun et al 2003). They can be applied in elementary chlorine and chlorine dioxide containing bleaching sequences, as well as in combination with oxygen, ozone and hydrogen peroxide (Filho 1998;Techapun et al 2003;Viikari et al 1990;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…따라서 xylanase 는 glucanase 및 mannanase와 함께 재생가능한 식물자원인 반 섬유소를 생물이 용이하게 대사할 수 있는 탄소원으로 전환시키 기 위해 활용되고 있으며, 제빵, 펄프와 제지가공 및 사료첨가용 효소로 이용되고 있다 (Subramaniyan and Prema, 2002).…”
unclassified